Identification of different tumor escape mechanisms in several metastases from a melanoma patient undergoing immunotherapy - Méndez, Rosa; Paschen, Annette; Schadendorf, Dirk (Cancer immunology immunotherapy, 2007)
The cytotoxic activity of T cells selects the outgrowth of tumor cells that escape from immune surveillance by different strategies. The different mechanisms that interfere with immune recognition and limit vaccination efficiency are still poorly understood. We analysed six cell lines established from different metastases of melanoma patient UKRV-Mel-20 for specific characteristics known to have an impact on the tumor-T cell interaction: (1) alterations in the HLA class I phenotype, (2) expression of Fas/CD95, and (3) expression of specific cytokines and chemokines. One of the cell lines, UKRV-Mel-20f, exhibited an HLA class I haplotype loss and just this cell line was also characterised by the expression of Fas/CD95 and of relatively high levels of proinflammatory chemokines suggesting that the cytotoxic activity of tumor-infiltrating T cells might have selected the outgrowth of this tumor cell variant. All other cell lines analysed showed no alterations in HLA class I expression, but, in contrast to UKRV-Mel-20f, expressed much lower levels of Fas/CD95 and of proinflammatory chemokines and some of them produced high levels of immunosuppressive TGF-β1. These results suggest that in patient UKRV-Mel-20, tumor cells interfere with T cell recognition by different strategies which might partially explain why this patient did not have a clinical response to an autologous tumor cell vaccine.